Enhanced Oxygen Reduction Activity on Carbon Supported Pd Nanoparticles Via SiO2. Issue 4 (23rd January 2019) - Bao, Zhikang; Zhou, Hu; Song, Xin; Gao, Yijing; Zhuang, Guilin; Deng, Shengwei; Wei, Zhongzhe; Zhong, Xing; Wang, Jianguo
Abstract: To improve Pd‐based catalysts activity and stability is still challenge although Pd‐based catalysts have attracted attention for oxygen reduction reaction (ORR) during recent years. In this study, we have prepared supported Pd on SiO2, in which conductive carbon was used by coprecipitation method Pd/SiO2 @C or physically mixed Pd/SiO2 .Pd/SiO2 @C (10 wt%) owned more outstanding catalytic activity, preferable durability, and stronger methanol tolerance capability in alkaline solution for ORR, which compared with commercial Pt/C (20 wt%) and Pd/C catalysts. We analyzed the morphology and electronic properties of the catalyst by SEM, TEM, XRD and XPS. It was found that the introduction of SiO2 changed the electronic structure of palladium, resulting in the production of electron‐rich Pd NPs, which was further confirmed by density functional theory calculations. Therefore, the introducing a small amount of SiO2 plays a vital role in facilitating the ORR activity of Pd‐based catalysts, which may be a new strategy to design new ORR catalysts and replace Pt‐based catalysts in fuel. Abstract : Silica to the rescue : The introduction of SiO2 changed the electronic structure of palladium. The resultant production of electron‐rich Pd NPs could greatly facilitate the oxygen reduction reaction.